Safety issues of tirzepatide (pancreatitis and gallbladder or biliary disease) in type 2 diabetes and obesity: a systematic review and meta-analysis - Zeng, Qingyue; Xu, Jiao; Mu, Xingyu; Shi, Yi; Fan, Hong; Li, Shuangqing (Frontiers in Endocrinology, 2023)
A systematic review and meta-analysis was conducted to synthesize the available data from clinical trials and assess the safety issues of tirzepatide (pancreatitis and gallbladder or biliary disease) in type 2 diabetes (T2D) and obesity.Methods: A systematic search was conducted in three electronic databases, namely Embase, PubMed, and the Cochrane Library, up until March 1, 2023, to identify randomized controlled trials (RCTs) comparing tirzepatide to either placebo or active hypoglycemic drugs in individuals with T2D and obesity. Heterogeneity was assessed using the I2 value and Cochran's Q test, and a fixed effects model was employed to estimate the safety profile of tirzepatide. The safety outcomes of interest, including pancreatitis, the composite of gallbladder or biliary diseases, cholecystitis, and cholelithiasis and biliary diseases, were evaluated. (The composite of gallbladder or biliary diseases incorporated cholelithiasis, cholecystitis, other gallbladder disorders, and biliary diseases.)Results: A total of nine trials with 9871 participants (6828 in the tirzepatide group and 3043 in the control group) that met the pre-specified criteria were included. When compared to all control groups consisting of basal insulin (glargine or degludec), selective GLP1-RA (dulaglutide or semaglutide once weekly), and placebo, an increased risk of pancreatitis was not found to be significantly associated with tirzepatide (RR 1.46, [95% CI] 0.59 to 3.61; I2 = 0.0%, p = 0.436). For gallbladder or biliary disease, the composite of gallbladder or biliary disease was significantly associated with tirzepatide compared with placebo or basal insulin (RR 1.97, [95% CI] 1.14 to 3.42; I2 = 0.0%, p = 0.558), but not with the risk of cholelithiasis, cholecystitis or biliary diseases.Based on the currently available data, tirzepatide appears to be safe regarding the risk of pancreatitis. However, the increased risk of the composite outcome of gallbladder or biliary diseases observed in RCTs warrants further attention from physicians in clinical practice.Systematic Review Registration: (https://www.crd.york.ac.uk/PROSPERO), identifier (CRD42023412400).